2019
DOI: 10.1155/2019/3507837
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of 4-Formylpyridinethiosemicarbazone and Structural and Biological Studies of Its Ni(II) and Cu(II) Complexes

Abstract: To understand the stability, chelation behaviour, and biological activity of 4-Formylpyridinethiosemicarbazone (H4FPT), it is important to recognize its interactive geometry. Hence, computational studies on geometrically optimized structures of thione and thiol forms of H4FPT were performed. Binary metal complexes of the ligand, H4FPT (L) with the Ni(II) and Cu(II) metal ions (M), were synthesized and characterized by various spectroanalytical techniques as elemental analysis, molar conductance, magnetic susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These results are in agreement with the theoretical calculations carried out on similar TSCs [97], which have shown that the thione tautomeric forms are stable, even in the presence of a solvent (MeOH). However, recent computational studies on 4-formylpyridine-TSC derivatives proved that both the thiol and thione forms are stable [98]. The 1 H NMR spectra of H2L1 showed the presence of two distinct signals for -(C=S)NH2 protons at 8.09 and 8.31 ppm, respectively, the latter presenting a NOESY correlation with the N(2)H proton at 11.64 ppm and suggested an E conformation.…”
Section: Synthesis and Characterization Of The Pro-ligandsmentioning
confidence: 96%
See 1 more Smart Citation
“…These results are in agreement with the theoretical calculations carried out on similar TSCs [97], which have shown that the thione tautomeric forms are stable, even in the presence of a solvent (MeOH). However, recent computational studies on 4-formylpyridine-TSC derivatives proved that both the thiol and thione forms are stable [98]. The 1 H NMR spectra of H2L1 showed the presence of two distinct signals for -(C=S)NH2 protons at 8.09 and 8.31 ppm, respectively, the latter presenting a NOESY correlation with the N(2)H proton at 11.64 ppm and suggested an E conformation.…”
Section: Synthesis and Characterization Of The Pro-ligandsmentioning
confidence: 96%
“…These results are in agreement with the theoretical calculations carried out on similar TSCs [97], which have shown that the thione tautomeric forms are stable, even in the presence of a solvent (MeOH). However, recent computational studies on 4-formylpyridine-TSC derivatives proved that both the thiol and thione forms are stable [98].…”
Section: Synthesis and Characterization Of The Pro-ligandsmentioning
confidence: 99%
“…Elemental analyses were performed with a Fisons-Carlo Erba 1108 microanalyser (CARLO ERBA Reagents SAS, Chaussée du Vexin, Val-de-Reuil, France). 1 H and 13 C NMR spectra were obtained as DMSO-d 6 solutions with a Varian Mercury 300 instrument (Varian Medical Systems, Inc, Palo Alto, CA, USA). IR spectra were recorded as KBr disks (4000-400 cm −1 ) or polyethylene-sandwiched Nujol mulls (500-100 cm −1 ) with a Bruker IFS-66v spectrophotometer (Bruker Corporation, Billerica, MA, USA).…”
Section: Physical Measurementsmentioning
confidence: 99%
“…However, they can also be coordinated in a tridentate or tetradentate manner, among other possibilities, when the aldehyde is functionalized or it is a bis-thiosemicarbazone. Clearly, the biological activity of the resulting complexes will be affected by the type of metal center and functionalization [13].…”
Section: Introductionmentioning
confidence: 99%